Recent abundance of bowhead whales in Isabella Bay, Canada - Hansen, R. G.; Heide-Jørgensen, M. P.; Laidre, K. L. (J. Cetacean Res. Manage., 2023)
An aerial survey of the late-summer distribution of bowhead whales, Balaena mysticetus, in Isabella Bay, Nunavut, Canada, was conducted on 19 September 2009. A total of 28 sightings were obtained during 155km of survey effort and >90% of the sightings were detected by both platforms. Corrections were made for whales that were submerged during the passage of the survey plane, resulting in an abundance estimate of 1,105 bowhead whales (95% CI: 532–2,294). No cow-calf pairs were observed confirming earlier observations that east Baffin Island is primarily visited by subadult and adult whales.